Fingermark visualisation on compostable polymers – A comparison among different procedures as an outcome of the 2020 collaborative exercise of the ENFSI Fingerprint Working Group. (June 2022) - Zampa, F.; Hilgert, M.; Mattei, A.; ,
Abstract: In 2020 the Fingerprint Working Group (EFP-WG) of the European Network of Forensic Science Institutes (ENFSI) undertook a collaborative exercise (CE) with the aim of assessing the ability in developing fingermarks on an item constituted of compostable polymers. The test was prepared and managed by the officially established advisory group. The characteristics of the CE are summarised. Different approaches emerged from the outcomes. Multi-Metal Deposition (MMD) was used as reference method for the assessment of the results. It demonstrated to be the more effective and consistent technique for fingermark visualisation on the specific kind of Mater-Bi® compostable polymer used for the test. Alternative techniques, such as Vacuum Metal Deposition (VMD), cyanoacrylate fuming, followed by Basic Yellow 40 dye staining or in its fluorescent forms demonstrated to be effective methods. However, it seems that the operational conditions need to be controlled in order to find the optimal ones. Conversely, data does not support the use of amino acid sensitive techniques. Highlights: A collaborative exercise was carried out in 2020 within ENFSI EFP-WG. The visualisation test was focused on a compostable polymer, specifically Mater-bi®. MMD demonstrated to be the more effective and consistent method. VMD and superglue followed by BY40 worked well. Data does not support the use of amino acid sensitive techniques.